1987
DOI: 10.1128/mcb.7.3.1004
|View full text |Cite
|
Sign up to set email alerts
|

An adenovirus type 5 E1A protein with a single amino acid substitution blocks wild-type E1A transactivation.

Abstract: The ElA gene of adenovirus type 5 encodes a 289-amino-acid (289R) protein that transactivates early adenovirus promoters. We showed that the 289R protein of the EIA missense mutant gene hr5 is novel in that it inhibits the wild-type (wt) ElA protein from stimulating transcription from each of the early viral promoters E2, E3, and E4. Since both the hr5 and wt genes produced similar levels of ElA proteins, the ability of hr5 ElA to block transactivation was attributed to the replacement of serine by asparagine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
25
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 58 publications
(60 reference statements)
0
25
0
Order By: Relevance
“…Mutants of a number of other viral trans-activator proteins such as ElA (36), tax (37), and VM65 (38) have been identified that inhibit the promoter activation of their wildtype proteins. These so-called transdominant mutants may play a role in creating cell lines "immune" to subsequent viral infection (38,39 (31)(32)(33)(34).…”
mentioning
confidence: 99%
“…Mutants of a number of other viral trans-activator proteins such as ElA (36), tax (37), and VM65 (38) have been identified that inhibit the promoter activation of their wildtype proteins. These so-called transdominant mutants may play a role in creating cell lines "immune" to subsequent viral infection (38,39 (31)(32)(33)(34).…”
mentioning
confidence: 99%
“…It remains unclear how the 289-aa protein stimulates its target promoters since a common inducible DNA response element has not been identified (18)(19)(20)(21)(22)(23). However, various studies strongly indicate that the mechanism of ElA trans-activation involves recruitment of one or more cellular transcription factors (24)(25)(26).…”
mentioning
confidence: 99%
“…However, ElA protein alone does not appear to bind DNA (51), and there is no obvious target element common to all ElA-inducible promoters (18)(19)(20)(21)(22)(23). On the other hand, bacterially produced ElA protein can exhibit DNA binding when mixed with cellular extracts (51,52), and there is compelling evidence that trans-activation by ElA occurs through an interaction with cellular transcription factors (24)(25)(26)53). In the presence of ElA, there is enhanced binding of a cellular factor upstream of the E2 promoter (24), and mutational analysis of the E1B promoter suggests that ElA increases the activity of the "TATA" box transcription factor (25).…”
mentioning
confidence: 99%
“…E1A 289R differs from E1A 243R by possessing conserved region 3 (CR3), a 46-amino-acid domain unique to 289R. CR3 is essential (13,20,24,30,34) and sufficient (15,25) for activation of viral early genes. Domains common to E1A 243R and E1A 289R are required for the growth-regulatory functions of E1A; these include the nonconserved N terminus (amino acids 1 to 39), CR1 (amino acids 40 to 80), and CR2 (amino acids 120 to 139) (28).…”
mentioning
confidence: 99%